ADVANCED BIO-SENSING SYSTEM FOR THERMAL AMBIENCE COMFORT - MATHE, REINALDO PEDRO (2018)
Conventional air conditioners are designed in such a way to maintain the indoor temperature and humidity at a desired level. They are designed to monitor indoors temperature not occupants comfort.